Тəрбие құнды байлық - Абдиркенова, А.Қ.; Ильясова, Г.Қ. (My University, 2016)
The views of scientists and poets considering the important problems of national upbringing. The effectiveness of the adoption of national bringing up in educational work at school. This article considers our ancestors influenced moral upbringing granting their attention to growing generation with the help of wise words.
Keywords: national upbringing; generation upbringing; national mind